An Analysis of Oil and Gas e-Learning Culture Pre-Covid-19, During and Post-Covid Era - Farha, Mohd; Sheikh Annuar, Sh A Rahim; Hock, Oo Yu (2021)
Since the 1920s, the Oil and Gas industry has adopted numerous approaches in learning. Increased collaborative knowledge management is a crucial effort in retooling the human capital. Remote learning via the digital platform is a win-win situation for the employer and employee. This paper discusses the challenges and recommendations of elearning. A qualitative study was conducted with a Malaysian Oil and Gas establishment to study its organizational management trends. The research findings and literature review highlighted three main phenomena of exchanging knowledge in this industry. Due to global expansion, virtual collaboration is a norm even before the COVID-19 pandemic.The findings suggest the adoption of an operational matrix to dynamic resource management as a digital platform (or technology) that is the catalyst to becoming a sustainable post-Covid organization. In part 2, all the sampling and data analysis will be demonstrated to confirm the e-learning approach to the proposed conceptual framework as described in part 1.